Annealed Importance Sampling for Ising Models with Mixed Boundary Conditions (Journal of Computational Mathematics, 2023)
This note introduces a method for sampling Ising models with mixed boundary conditions. As an application of annealed importance sampling and the Swendsen-Wang algorithm, the method adopts a sequence of intermediate distributions that keeps the temperature fixed but turns on the boundary condition gradually. The numerical results show that the variance of the sample weights is relatively small.
Keywords: Ising model; Annealed importance sampling; Swendsen-Wang algorithm.